Implementation of Risk Management in Property Projects - I Wayan Muka; Agung Wibowo (Journal of Infrastructure & Facility Asset Management, 2021)
Abilitythe company's organization to manage risk is very dependent on the characteristics of the project and must take into account vulnerabilities during risk identification and assessment. In the property development process, vulnerability is a system characteristic that will create the possibility of damage, danger and failure. Vulnerability is a system that functions as a control and manageability. Risk is a function of threat values, consequences, and vulnerability. Risk is a function of threat values, consequences, and vulnerability. The purpose of risk management is to create a level of protection that alleviates vulnerability to threats and potential consequences, thereby reducing risk to an acceptable level. The implementation of risk management must be an integral part of the implementation of the company's management system. The risk management process is one step that can be taken to create continuous improvement.The stages carried out in this study include: identification of the source of risk, the stage of identification of risk factors, the stage of identification of the level of hazard, the stage of identification of the level of vulnerability, the stage of identification of the level of capacity, the stage of risk analysis, and the determination of priority risks. Conceptually, the method proposed in this study refers to the key steps of risk management which include identification, qualitative risk analysis in the property development process. Data collection was carried out through interviews and filling out questionnaires by resource persons involved in property development in the tourism area of Nusa Dua Resort ITDC Bali Province. Risk factors that are given priority for ongoing mitigation and monitoring are: interest rate risk and inflation, risk of development cost analysis, risk of final design, risk of land maturation and risk of development financing targets. It can be concluded that overall the level of risk in developing the Nusa Dua resort area is acceptable (IPR <0.24) and the development of the Nusa Dua Resort area is indeed feasible to be developed or built.